The Geometric Design of Horizontal Curves Using The Autocad Civil 3D® Method: A Case Study of Trans Flores Roads - Safira Salsabila; Andri Irfan Rifai; Mohamad Taufik (International Journal Labs, 2022)
In general, the geometric planning of roads is done manually using drawing tools and mathematical techniques. When done manually, geometric design is complicated, time-consuming, and prone to errors. Therefore, this study will use AutoCAD Civil 3D®. This study aims to redesign the Trans Flores road because of the frequent accidents found on curves and climbs and the current road drops on the Trans Flores road. This study will use research methods using secondary data and qualitative research methods. When designing geometric roads using AutoCAD Civil 3D®, data from Google Maps, Google Earth, and Global Mapping is also required. This research will focus on the 3.5 km of road traffic starting from Sta 0+000 to Sta 3+500. The result of this study is that corners P1-P4 are planned with the type of Bend S-C-S. By using AutoCAD Civil 3D®, this research can be completed quickly and accurately.